1985
DOI: 10.1021/bi00348a010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of halothane on the natural-abundance carbon-13 NMR spectra of excised rat brain

Abstract: Halothane increases the intensity of the 30.5- and 129-ppm resonances in 13C nuclear magnetic resonance spectra of excised rat brain, of phospholipid vesicles prepared from chloroform-methanol extract of rat brain, and of brain excised from rats anesthetized with halothane. The 13C spin-lattice relaxation times of the 30.5- and 129-ppm resonances are increased in excised brain, or phospholipid vesicles, upon addition of halothane, and they are also increased in brain excised from rats anesthetized with halotha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This concentration of halothane is severalfold higher than the pharmacological doses of anesthetic. A halothane concentration of 3.34 mM has been detected in the brain of halothane-anesthetized rats (20). We have recently observed that with lower concentrations of halothane (1 mM final, added in dimethyl sulfoxide), [Ca2+Ii was again increased in lymphocytes from MH-susceptible pigs but not from normal pigs (not shown).…”
Section: Methodsmentioning
confidence: 89%
“…This concentration of halothane is severalfold higher than the pharmacological doses of anesthetic. A halothane concentration of 3.34 mM has been detected in the brain of halothane-anesthetized rats (20). We have recently observed that with lower concentrations of halothane (1 mM final, added in dimethyl sulfoxide), [Ca2+Ii was again increased in lymphocytes from MH-susceptible pigs but not from normal pigs (not shown).…”
Section: Methodsmentioning
confidence: 89%